The Effect of Teacher’s Teaching Style in Araling Panlipunan on Student’s Motivation of Grade 8 Students in Sta. Cruz South High School - Ofiaza, Evangeline S. (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
The study shows that shows, out of ninety (90) respondents, there is an equal number of respondents when grouped according to gender. The study revealed that 80% of the respondents acknowledge the importance effective teaching styles to motivate the students. The stiudy further confirm that 3.7% of the respondents, considered Araling Panlipunan fun and interesting. It was also confirmed in the study that 3.8% of the respondents participated actively in Araling Panlipunan. The study revealed that majority of the respondents had the view that having effective teaching-styles in motivating students had a high impact on the academic performance. Based on the findings of the study, the following recommendations are made:Faculty staffs are encouraged to adapt new trends of teaching in order to inspire our students embracing Araling Panlipunan subject. It is further recommended that Araling Panlipunan teachers should not only using a pen and paper materials in teaching, instead think of an effective materials were in students become more motivated in exploring ideas like projectors and more. Conduct future studies to develop more teaching styles to motivate students to study Araling Panlipunan.